“A la vuelta de la esquina se baila tango”: usos y discusiones en torno a la práctica del baile tanguero en la ciudad de Santiago (2000-2012) - Cristián Molina Torres (Resonancias, 2013)
This article describes the presence of tango in Santiago de Chile, where tango culture resides primarily as dance practice. During the last decade, tango danced in Santiago has experienced changes in response to new trends and corporal practices that have come out of Buenos Aires. These new practices have modified the way of understanding and experiencing tango, even causing a crisis in the uses of the dance in the places that had traditionally fostered the local tango culture.